Mitochondrial Functional Changes Characterization in Young and Senescent Human Adipose Derived MSCs - Stab, Bernd R.; Martinez, Laura; Grismaldo, Adriana; Lerma, Alejandra; Gutiérrez, María L.; Barrera, Luis A.; Sutachan, Jhon J.; Albarracín, Sonia L. (Frontiers in Aging Neuroscience, 2016)
Mitochondria are highly dynamic organelles that in response to the cell’s bio-energetic state continuously undergo structural remodeling fission and fusion processes. This mitochondrial dynamic activity has been implicated in cell cycle, autophagy and age-related diseases. Adult tissue-derived mesenchymal stromal/stem cells present a therapeutic potential. However, to obtain an adequate mesenchymal stromal/stem cell number for clinical use, extensive in vitro expansion is required. Unfortunately, these cells undergo replicative senescence rapidly by mechanisms that are not well understood. Senescence has been associated with metabolic changes in the oxidative state of the cell, a process that has been also linked to mitochondrial fission and fusion events, suggesting an association between mitochondrial dynamic and senescence. In the present work, we studied the mitochondrial structural remodeling process of mesenchymal stromal/stem cells isolated from adipose tissue in vitro to determine if mitochondrial phenotypic changes are associated with mesenchymal stromal/stem cell senescence. For this purpose, mitochondrial dynamics and oxidative state of stromal/stem cell were compared between young and old cells. With increased cell passage, we observed a significant change in cell morphology that is associated with an increase in β-galactosidase activity. In addition, old cells (population doubling seven) also showed increased mitochondrial mass, augmented superoxide production, and decreased mitochondrial membrane potential. These changes in morphology were related to slightly levels increases in mitochondrial fusion proteins, Mitofusion 1 (MFN1) and Dynamin-realted GTPase (OPA1). Collectively, our results showed that adipose tissue-derived MSCs at population doubling seven develop a senescent phenotype that is characterized by metabolic cell changes that can lead to mitochondrial fusion.